The Politics and Governance of Basic Education : A Tale of Two South African Provinces - Levy, Brian; Cameron, Robert; Hoadley, Ursula; Naidoo, Vinothan; Levy, Brian; Cameron, Robert; Hoadley, Ursula; Naidoo, Vinothan (Oxford, UK Oxford University Press, 2018)
Uses cutting edge and multidisciplinary approaches to analyse the politics of service provision and serves as a model for how similar research can be conducted in other countries and sectors - An in-depth, microlevel analysis that develops the high-profile South African discourse on the interaction between governance and policy - Systematically anchored in innovative thinking on how to achieve gains in politically complex settings
English
Keywords: Republic of South Africa; Education; Politics & government; politics of service provision; South Africa; governance; policy; Apartheid; Bureaucracy; Eastern Cape; Kenya; Western Cape